2020
DOI: 10.1029/2020ja028142
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of the Pedersen Conductance in the Jovian Aurora From Juno‐UVS Spectral Images

Abstract: Ionospheric conductivity perpendicular to the magnetic field plays a crucial role in the electrical coupling between planetary magnetospheres and ionospheres. At Jupiter, it controls the flow of ionospheric current from above and the closure of the magnetosphere‐ionosphere circuit in the ionosphere. We use multispectral images collected with the Ultraviolet Spectral (UVS) imager on board Juno to estimate the two‐dimensional distribution of the electron energy flux and characteristic energy. These values are fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 43 publications
12
32
0
Order By: Relevance
“…These results are in agreement with one‐dimensional models of auroral Pedersen conductance (Hiraki & Tao, 2008; Millward et al., 2002) that have shown that the amount of H 3 + ions is the key quantity controlling the Pedersen conductance. In turn, the H 3 + content in each hemisphere varies nearly proportionally to the square root of the precipitated auroral power (Gérard et al., 2020; Tao et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are in agreement with one‐dimensional models of auroral Pedersen conductance (Hiraki & Tao, 2008; Millward et al., 2002) that have shown that the amount of H 3 + ions is the key quantity controlling the Pedersen conductance. In turn, the H 3 + content in each hemisphere varies nearly proportionally to the square root of the precipitated auroral power (Gérard et al., 2020; Tao et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“… the ionization rate profile q(z) is calculated versus altitude using the auroral electron energy flux Fe and mean energy E 0 values for each bin from the analytical expressions given by Hiraki and Tao (2008) the q(z) profiles are inputs to an ionosphere model describing the generation and loss of the different ion species (Gérard et al., 2020). The resulting vertical distributions of H 3 + , hydrocarbon ions and electrons are then calculated for each UVS latitude‐longitude bin the altitude‐dependent Pedersen conductivity σ P is obtained by adding the electron and ion contributions based on the classical Pedersen conductivity formulation combining the ion‐neutral and the electron‐neutral contributions: …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three main sources of uncertainty affect estimates of the total emitted power by the H 2 molecules in the UV: 1) systematic calibration uncertainties estimated on the order of 16% (Gérard et al., 2020), 2) shot noise uncertainty, which depends on the number of counts in the region of interest and is typically below 5% for the small spots and below 1% for the larger dawn storm features, and 3) the selection uncertainty, which depends on the way the region of interest is defined and which may reach up to 15%. The quadratic sum of all these uncertainties can be rounded to a reasonable value of 25% for power estimates.…”
Section: Image Processingmentioning
confidence: 99%